Recent developments in the diagnosis and treatment of covert/minimal hepatic encephalopathy. (2nd April 2016) - De Rui, M.; Montagnese, S.; Amodio, P.
ABSTRACT: The terms minimal hepatic encephalopathy and covert hepatic encephalopathy are defined. Clinical assessment is unreliable and both require the use of diagnostic tools. Of these, psychometric tests are the most widely used. They require proper standardization and may be biased by patient cooperation or lack thereof. The measure of the critical flicker frequency and of the electroencephalogram, possibly quantified, are also useful. The alteration of any of them is not strictly parallel in size and may vary from patient to patient. When possible, the use of multiple measures might increase diagnostic reliability. These functional measures should be interpreted within the clinical/biochemical profile of the patient to exclude other disorders. A flow chart for treatment is proposed on the basis of current knowledge.